The Deep South - Logan, William Bryant; Muse, Vance; Kennedy, Roger G. (New York Stewart, Tabori & Chang, 1989)
Travel guide of the American Deep South.
Introduction : New Orleans and the Bayou Country : The River Road and Northern Louisiana : Mississippi : Alabama : Savannah and the Coastal Plain : Atlanta and Northern Georgia : Heart of the Piedmont : Northern Florida : Central and Southern Florida : Notes on Architecture : Index
Includes Index
Keywords: Description and travel -- Southern States -- 1981; Historic sites -- Southern States -- Guidebooks; Description and travel -- Gulf States -- Guidebooks; Historic sites -- Gulf States